INTERPRETATION OF WORDS OF RESPECT IN ENGLISH AND UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Respect is one of the fundamental aspects of human interaction. Expressing respect through language is an integral part of communicative culture. Words and expressions that convey respect in English and Uzbek vary, reflecting differences in their linguistic, cultural, and social contexts. This article analyzes the main linguistic means of expressing respect in both languages, their usage characteristics, functions, and significance in communicative contexts. Additionally, the study highlights the relationship between language and culture and presents strategies for demonstrating respect in communication. This research can be useful for linguists, translators, and communication specialists.